Investigation of gas–solids flow characteristics in a conical fluidized bed dryer by pressure fluctuation and electrical capacitance tomography. Issue 11 (17th August 2016) - Ge, Ruihuan; Ye, Jiamin; Wang, Haigang; Yang, Wuqiang
ABSTRACT: It is important to investigate the gas–solids flow characteristics of fluidized bed drying processes to improve the operation efficiency and guarantee the product quality. This paper presents research into fluidized bed drying processes measured by high-frequency differential pressure fluctuation and electrical capacitance tomography (ECT). Power spectra analysis is combined with dynamic calibration for ECT to reveal the complex gas–solids flow behavior. Bubble characteristics are visualized by cross-sectional and quasi-3D ECT images. In addition, results by discrete wavelet transform analysis are given and compared with the analysis results of previous sections. It has been found that bubbles would coalesce in different ways under different operation conditions, and discrete wavelet transform sub-signals of ECT measurements are sensitive to particle moisture. This work reveals the complex hydrodynamic behavior in the fluidized bed dryer and provides valuable information for process control.